2014
DOI: 10.1590/1678-775720130574
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of fluoride release from experimental TiF4 and NaF varnishes in vitro

Abstract: Fluoride varnishes play an important role in the prevention of dental caries, promoting the inhibition of demineralization and the increase of remineralization.Objective This study aimed to analyze the amount of fluoride released into water and artificial saliva from experimental TiF4 and NaF varnishes, with different concentrations, for 12 h. Material and Methods Fluoride varnishes were applied on acrylic blocks and then immersed in 10 ml of deionized water and artificial saliva in polystyrene bottles. The ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 26 publications
3
18
0
Order By: Relevance
“…This conclusion is supported by previous research, which states that products that increase fluoride ion concentrations will also increase remineralization potential and produce bioavailability of fluoride ion concentration in saliva [10]. The application of fluoride varnish may lead to the formation of a calcium fluoride (CaF 2 ) layer in enamel, which can be a mineral reservoir and releases fluoride while caries are forming [8].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…This conclusion is supported by previous research, which states that products that increase fluoride ion concentrations will also increase remineralization potential and produce bioavailability of fluoride ion concentration in saliva [10]. The application of fluoride varnish may lead to the formation of a calcium fluoride (CaF 2 ) layer in enamel, which can be a mineral reservoir and releases fluoride while caries are forming [8].…”
Section: Discussionsupporting
confidence: 68%
“…Fluoride levels influence the incidence of caries overtime. The low fluoride ion levels in saliva, approximately 0.04 ppm, provide a strong protective effect against dental caries [8]. Therefore, low levels of fluoride in saliva are an important parameter when looking at the effectiveness of fluoride agents.…”
Section: Discussionmentioning
confidence: 99%
“…It is already known that the amounts of alkali-soluble fluoride on enamel increase with a pH decrease [Saxegaard and Rölla, 1988]. Furthermore, Comar et al [2014] demonstrated that TiF 4 varnish has the ability to release more fluoride than NaF varnish in water and saliva (Klimek formulae) due to its low pH, providing more F to react with enamel. Previous studies have shown that the protective effect of TiF 4 is dependent on its low pH for enamel erosion protection [Wiegand et al, 2009;Hove et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…Products that promote greater fluoride release overtime are effective in preventing and controlling dental caries [2,14]. Therefore, determining the fluoride concentration present in saliva after topical application of professional use products in necessary to assess their efficacy [6,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%